A 2H-MoS2/carbon cloth composite for high-performance all-solid-state supercapacitors derived from a molybdenum dithiocarbamate complex. Issue 34 (10th August 2021) - Yan, Zhishuo; Zhao, Jixing; Gao, Qingsheng; Lei, Hao
Abstract : A 2H-MoS2 /CC composite is obtained by hydrothermal treatment and subsequent single-source pyrolysis of a Mo dithiocarbamate complex. The electrode is assembled into a high-performance symmetric all-solid-state supercapacitor. Abstract : A molecular complex Mo2 O2 (μ-S)2 (Et2 dtc)2 (dtc = dithiocarbamate) is prepared and loaded onto carbon cloth (CC) through facile solvothermal treatment, followed by subsequent single-source pyrolysis. This results in a highly porous 2H-MoS2 /CC composite with a sponge-like stacked lamellar morphology. Due to its high porosity and unique nano/microstructure, the MoS2 /CC composite exhibits a specific capacitance of 550.0 F g −1 at 1 A g −1, outperforming some 1T-MoS2 based electrodes. The composite is further assembled into a symmetric all-solid-state supercapacitor, which can be operated stably at a wide potential window and shows a specific capacitance of 127.5 F g −1 at 1 A g −1 . In addition, the device delivers a high energy density of 70.8 W h kg −1 at 1 kW kg −1, which still remains 15.0 W h kg −1 at 18.0 kW kg −1 . 75% of the performance of the device can be retained after 8000 cycles. Such remarkable electrochemical performance is attributed to its novel nano/microstructures with a large surface area, convenient ion transport pathways, enhanced conductivity, and improved structural stability. Thus, this work demonstrates a highly promising dithiocarbamate-based single-precursor pyrolysis route towards the fabrication of metal sulfides/carbon composites for energy storage applications.